The effect of nanoparticles on development parameters in a plant species: durum wheat (Triticumdurum Desf). - Dr Nadia CHIAHI; Dr BOULOUIDENINE Manel; Pr Louhichi BRINIS (Scholars Research Library, 2016)
In this study we were interested in assessing the impact of ZnO nanoparticles and their effects on durum wheat (Triticum durum Desf). The effect of ZnO is evaluated in three varieties of wheat (Boussallem, Gtadur and Ouarsenis), the three varieties are represented by V1, V2 V3 and through a range of development settings, made in the laboratory. The selected varieties were exposed to increasing concentrations of NPs ZnO (0.01mg / ml, 0.05mg / ml, 0.1mg / ml, and 0.5mg / ml). The results show that the presence of ZnO based NPs can exert a stimulating effect according to the effect inhibitor concentration and the parameter under study, it is concluded that, except for a decrease in root elongation: strong effect concentration. We can advance the development of wheat seedlings was not much affected by the presence of ZnO NPs in their experimental medium sometimes it provoked a stimulating effect (increasing the percentage of germination).
durum wheat (Triticumdurum Desf)
Keywords: Nanoparticles; ZnO; germination; vegetable species; concentrations